Stale seedbed techniques for management of weedy rice (Oryza sativa f spontanea L.) in direct seeded rice - M., Ameena (Annals of Agricultural Research, 2016)
Weedy rice (Oryza sativa f spontanea) is a weedy form of cultivated rice which has recently emergedas a serious threat to the direct seeded kharif rice in Kerala. It competes aggressively with the crop,leading to drastic yield reduction besides contaminating the produce and the field. Considering theseverity of the problem, field experiments were laid out to evolve an effective management strategyfor weedy rice through integrated approach involving stale seedbed with herbicides and ploughingoperations in a heavily weedy rice infested farmers' field. The treatments comprised of 4 differenttypes of stale seed bed (SSB) technique, viz. SSB with and without stimulatory rice crop anddestruction with a total weed killer viz. glyphosate or paraquat followed by dry or wet ploughing.The studies revealed that sowing of rice seeds have no significant influence in stimulating germinationof weedy rice. In general, stale seedbed treatments resulted in reduction in weedy rice plant densityto the tune of 39.83 % to 63.72% during first year and 58.27 to 76.99% during second year. Staleseedbed coupled with glyphosate application followed by wet ploughing the field and wet seedingrecorded the lowest weedy rice population and highest rice yields of 1.70 and 1.71 t/ha during boththe years. Yield loss under unweeded situation measured by weed index was 75.60 with a BCR of0.87 during first year and yield loss touched its peak during second year with a BCR of 0.70 whichindicated the harmful effect of seed bank accumulated during previous year in unweeded areas.Stale seedbed with glyphosate application followed by wet ploughing under continuous submergencecould be recommended as an effective preventive management strategy for weedy rice managementin direct seeded rice.